The Effectiveness of Sprint Training and Hollow Sprints in Improving Leg Muscle Power in Players of the Tumbak Raya Mitra Soccer Club - Achmad Paturusi; Saputra A.S Paturusi; Nofie Sondakh (Ridwan Institute, 2026)
The Effectiveness of Sprint Training and Hollow Sprint on Increasing Leg Muscle Power in Tumbak Raya Southeast Minahasa Football Club Players. This study aims to measure and analyze empirical data on the effectiveness of sprint training and hollow sprint on improving leg muscle power ability in Tumbak Raya Southeast Minahasa football club players. The method used is the